Na arena da luta de classes a mais valia sob o crivo da análise do discurso - Duarte, Gílber Martins (2013)
This thesis aims at defending, as a central point, that, one of the devices used by discursive-ideological-legal-economic process to reproduce production relations in capitalism, works under the interpelation which tries to erase-legitimate-naturalizeeternalize-( make seems to be unavoidable)-(make seems to be necessary) the surplus value, that is to say, the exploration of labor time worker, not paying them for such endeavor, in order to benefit production means owners. To demonstrate the relevance of such central thesis, it was researched a corpus, composed by linguistic materialities captured from some so called capitalist institutions (discursive extracts and sequences collected from: i) company sites; ii) traditional partisan-political discourses and iii) antimarxist theories). It was also taken as corpus, linguistic materialites collected from combative organisations from working class (discursive extracts and sequences collected from i) socialist left journals; ii) alternative lyrics, poems, and marxist comics and iii) partisan political discourses from socialist left parties). This thesis also aims at demonstrating the relevance of critical reading, under the framework of Discourse Analysis, several discursive-ideological-legal-economic practices which constitute surplus value framework. It was also demonstrated that it is needed to read critically theories which deny marxism, once such theories do not approach clearly the capitalist contradiction of surplus value, indirectly corroborating to a perpetuation of such social phenomenon which is founded in worker exploration. The great sense effect which emerges is the need to unveil and to emphasize, critically, several discursivities concerned to surplus value, once such discursivities define position makings in class struggle, that is to say, position makings in transformation/reproduction struggles in production relations. Such struggle which any subject is involved, according to Pêcheux (1997). Thus, adopting a marxist and revolutionary Discourse Analysis framework, the pecheutean orientation, these discursivities are introduced direct or indirectly, as a support to capture suspected surplus value extractions, showing they reproduce production relations as natural, eternal, genuine, necessary and unavoidable practices. This research also aims at showing that marxism continues to be a reference of critical reading close to Discourse Analysis scope, in spite of the ones which insist in denying, erasing or trying to forget such reference.